2004
DOI: 10.1016/s0928-8244(03)00358-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of lethal respiratory vaccinia infections in mice with interferon-α and interferon-γ

Abstract: The antiviral efficacy of interferons (IFNs) was evaluated using a vaccinia intranasal infection model in mice in this study. We provide evidence that intranasal administration of IFN-alpha and IFN-gamma (days -1 to +3) resulted in 100 and 90% survival against a lethal respiratory vaccinia infection (8 LD50) in mice, respectively; whereas no animals in the placebo group survived through the study period (21 days). The IFN treatment consisted of a single daily dose of 5x10(3) U per mouse for 5 consecutive days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…8C and D). However, in the case of Ebola virus, postchallenge treatment was more efficacious (53), and other studies have shown that multiple treatments with IFN-␥ protected mice from a lethal challenge with vaccinia virus via the respiratory route (71). EHV-1 infection did not cause a decrease in the viability of IFN-␥-treated MH-S alveolar macrophages (data not shown).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…8C and D). However, in the case of Ebola virus, postchallenge treatment was more efficacious (53), and other studies have shown that multiple treatments with IFN-␥ protected mice from a lethal challenge with vaccinia virus via the respiratory route (71). EHV-1 infection did not cause a decrease in the viability of IFN-␥-treated MH-S alveolar macrophages (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…Levels of the IFN-␥ gene and 16 antiviral ISGs were significantly upregulated upon pathogenic RacL11 challenge ( Table 3), suggesting that immunization with attenuated EHV-1 KyA induces innate immune responses upon pathogenic EHV-1 challenge within 2 weeks postimmunization that protect mice. EHV-1 KyA immunization protected CBA mice from pathogenic RacL11 challenge at 4 weeks postimmunization, and the KyA infection elicited protective humoral and cell-mediated immune responses (14,17,71), indicating that immunization with attenuated EHV-1 KyA protects mice from pathogenic RacL11 challenge through adaptive immune responses. It is possible that immunization with attenuated EHV-1 KyA protects horses from pathogenic EHV-1 challenge by both the innate and adaptive immune responses.…”
Section: Discussionmentioning
confidence: 95%
“…Nonetheless, VACV differs from ECTV in that the VACV spread from the primary site of infection is more efficiently restricted in immunocompetent mice (31,76,79). The administration of exogenous IFN-␥ prevents lethal respiratory VACV infection in mice and reduces the virus titer in the lungs about 1,000-fold (41). In contrast, ECTV disseminates via the lymphatics and undergoes a primary viremia that is followed by an extensive virus multiplication in visceral organs.…”
Section: Discussionmentioning
confidence: 99%
“…These proinflammatory cytokines and antiviral factors may contribute to the reduced VACV production in infected M1 macrophages. In fact, IFN treatment can greatly diminish VACV titers in vivo (57), despite the fact that poxviruses have evolved numerous strategies to counter host antiviral responses (58). Thus, the IFN-related pathways may also contribute to the reduced viral titer observed from M1 macrophages.…”
Section: Discussionmentioning
confidence: 99%